Hmac Security Implementation in Iec 61850 Sampled Values for Power System Infraestructure - Chavez-Orostica, H; Valencia-Cordero, C (Institute of Electrical and Electronics Engineers Inc., 2024)
This work implements a Hash Message Authentication Code (HMAC) to secure Sampled Values (SV) in the IEC 61850 protocol, addressing cyber-attack vulnerabilities in digital substations. Using Python s Scapy, algorithms were developed to inject and capture multicast SV traffic. HMAC with SHA- 256 effectively protected against data tampering, allowing only authorized devices to authenticate messages. Experimental results confirmed real-time attack detection and mitigation. This research enhances SV message security in line with IEC 62351 guidelines. © 2024 IEEE.